The effect of vascular endothelial growth factor-1 expression on survival of advanced colorectal cancer patients. Issue 1 (1st January 2017) - Bendardaf, Riyad; El-Serafi, Ahmed; Syrjänen, Kari; Collan, Yrjö; Pyrhönen, Seppo
ABSTRACT: Colorectal cancer is third leading cause of cancer mortality. About 60% of patients had already developed metastasis at the time of diagnosis. Vascular endothelial growth factor (VEGF) is crucial for the development of neovascularization and hence metastasis. This study aimed at investigating the relation between the expression of VEGF in biopsies from surgically dissected colon cancer and the survival of those patients. Biopsies were collected from 86 patients with advanced colon cancer and sections were stained by immunohistochemistry for VEGF. Patients received chemotherapy after the operation and were followed up for disease progression and survival. The clinical data were statistically analyzed with respect to the immunohistochemistry results. The survival of the patients was significantly longer in the patients for whom biopsies showed negative or weak expression of VEGF in comparison to those with moderate to high expression (p-value = 0.04). The expression of VEGF was more frequent in the patients who died as a consequence of the disease in comparison to the 10-year survivors. In conclusion, VEGF could be related to the survival of the patients with colorectal carcinoma and should be considered as a predictor of the prognosis.